THE ANALYSIS STUDY OF EFFECTIVENESS AND SAFETY OF ORAL SILDENAFIL CITRATE FOR TREATMENT OF ERECTILE DYSFUNCTION : A COMPREHENSIVE SYSTEMATIC REVIEW - Nugraha, Dhimas Mohammad Fajar; Akmalia, Tsalitsa Laili (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Erectile dysfunction (ED) is a medical condition affecting men's sexual performance and well-being. Sildenafil citrate, a specific inhibitor of phosphodiesterase type 5, is approved for treating ED. The efficacy and safety of oral sildenafil citrate in treating ED are crucial for successful treatment procedures. Understanding the relationship between the efficacy and safety of oral sildenafil citrate can help develop successful treatment procedures for ED patients.Methods: This systematic review adhered to the PRISMA 2020 guidelines and primarily examined entire English literature published between 2000 and 2024. Only editorials and review articles published in the same publication as the submission were accepted if they possessed a Digital Object Identifier (DOI). A variety of online platforms, including ScienceDirect, PubMed, and SagePub, were utilized to gather the relevant literature.Result: The study analyzed more than 2000 papers from reputable sources such as Science Direct, SagePub, and PubMed. After deciding to subject eight publications to additional inspection, a thorough evaluation of the entire body of literature was carried out.Conclusion: Sildenafil, a potent treatment for erectile dysfunction (ED), has been found to be effective in improving men's psychosocial aspects. It is an inhibitor of PDE5, a condition that affects men's emotional well-being. The study also found that the firmness of erections was linked to improvements in psychosocial aspects. Sildenafil can be used interchangeably with tablets, providing a convenient alternative for those with difficulty swallowing. However, follow-up for men with ED is often inadequate due to improper doses and lack of understanding.